THE DETECTION OF THE TIME OF CONVERSION FROM VEGETATIVE TO REPRODUCTIVE GROWTH IN Swainsona formosa (FABACEAE) - Zulkarnain Zulkarnain (Jambi University, Fakultas Pertanian, Program Studi Agroekoteknologi, 2018)
The induction of chromosome doubling using antimitotic chemical will only be effective when the substance is applied at vegetative growth phase, as it works only during mitotic division within cells of actively growing tissues. Therefore, this investigation was carried out to determine the precise conversion time from vegetative into reproductive growth stage, that in turn can be used as a reliable reference for the application of antimitotic chemicals in doubling the chromosome number in Swainsona formosa. The conversion from vegetative to reproductive growth in Swainsona formosa was successfully determined with particular emphasis on the effect of different photoperiods. Although photoperiod affected the time required for first flower initiation, the number of nodes before the plant entering the reproductive stage was not affected by photoperiod and presumed to be set genetically. It was found that under artificial photoperiods of 16, 12 and 8 hours the 12th and 11th nodes were the critical nodes for the main and side stems, respectively. Meanwhile the 10th and 8th nodes were found to be critical for main and side stems of plants grown under natural photoperiods ranging from 12 to 16 hours during their life cycle. Histological examination indicated that when the plants were grown under 12 – 16 hours photoperiods the first floral bud formation was initiated within 56 – 60 days after germination, thus this period was considered as the critical time for the conversion from vegetative to reproductive growth in S. formosa. Keywords: Sturt’s desert pea, legume, ornamental plant, plant breeding.